Traditionalism Nazhir Kyai On Waqf Asset Development In Bangkalan Madura (ZISWAF: Jurnal Zakat dan Wakaf, 2021)
This research aims to identify the model of waqf asset management by religious leaders figure (kyai) in Madura, which serves to supports and optimization asset waqf utility nationally that has not been well empowered. This study focus on, (1) knowing the management and development of waqf capital assets by Kyai as Nazhir in Bangkalan, (2) to find out the analysis off waqf asset development model in order to increase benefit of waqf assets in Bangkalan. This research uses qualitative approach. Data retieval techniques with documentation, in-depth interviews on the management of waqf asset in Bangkalan, which using component analysis on waqf core principles standards.The results of the research showed that waqf assets managed by kyai were transfered to posterity without going through the changing nazhir process, which impacted on the unfulfilled aspects on waqf development, which based on aspects of knowledge, training recruitment, rewards, and aspects of coaching and supervision